Glycoprotein imprinted polymer based on imidazole ionic liquid monomer containing boric acid functional group as well as preparation method and application of glycoprotein imprinted polymer
By designing functional monomers with long-range non-covalent and short-range covalent interactions and binding surface molecular blotting technology, a glycoemi-blot polymer based on boric acid-containing functional group imidazole ionic liquid monomer was prepared, which solved the problems of insufficient identification specificity and limited adsorption capacity in the prior art, and achieved the effect of efficient identification and separation of glycoproteins.
Patent Information
- Application Number
- CN202510028077.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-25
AI Technical Summary
In the absence of specificity of glycoemic molecular imprinted polymers, existing glycoemic molecular imprinted polymers, are difficult to meet the needs of efficient separation and enrichment of glycoproteins due to problems such as insufficient identification specificity, limited adsorption capacity, poor carrier performance and complex preparation process.
Using innovative technical solutions based on boric acid-containing functional group imidazole ionic liquid monomer (PBA-IL) and lignocellulose sponge-loaded UiO-66 composite carrier (WCS@UiO-66), we prepared a blot polymer that efficiently recognizes and isolates glycoemi-economic by designing functional monomers that combine long-range non-covalent and short-range covalent interactions, and combined with surface molecular blotting technology and template immobilization strategies.
The identification specificity and blot efficiency of imprinted polymers are significantly improved, the adsorption capacity is improved, the preparation process is simplified, energy consumption is reduced, the dispersion and recyclability of the material are enhanced, and the applicability and economicality in actual sample processing is improved.
Smart Images

Figure CN119684674A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a glycoprotein imprinted polymer, in particular to a glycoprotein imprinted polymer based on an imidazolium ionic liquid monomer containing a boronic acid functional group, and a preparation method and application thereof. Background Art
[0002] Glycoproteins are important biomolecules in biological systems and are widely involved in processes such as cell communication, immune response, signal transduction, and disease progression. Due to their importance in biology, medicine, and biotechnology, the specific identification and efficient separation of glycoproteins have become key research areas. However, due to the complex structure and diverse glycosylation patterns of glycoproteins, existing separation and identification technologies are usually difficult to meet the needs of practical applications.
[0003] Molecularly imprinted polymers (MIPs), as an artificially designed recognition material, have become an effective tool for separating and identifying biomacromolecules due to their strong molecular recognition ability, high chemical stability and low preparation cost. Traditional MIPs technology is mostly used for the separation of small molecule targets, and its applicability to macromolecular templates such as glycoproteins is still limited. This is mainly due to the complexity of macromolecular templates, which leads to low efficiency of interaction sites during the imprinting process. At the same time, how to balance the high recognition, high adsorption capacity and convenience in industrial operation of MIPs is still a difficulty in current research.
[0004] In recent years, metal organic framework (MOFs) materials have been gradually applied to the preparation of molecular imprinted polymers due to their high specific surface area, abundant active sites and good structural controllability. For example, UiO-66, as a typical MOFs, has been shown to effectively improve the adsorption performance and recognition efficiency of MIPs. In addition, surface molecular imprinting technology (SIT) combined with template immobilization (TIM) has been widely used to improve the imprinting efficiency of macromolecular templates, which greatly reduces the mass transfer resistance of template molecules by limiting the imprinting sites to the polymer surface or near the surface. Although these technologies have made certain progress, the existing technologies still have the following significant defects in the preparation and application of glycoprotein MIPs:
[0005] (10) Existing functional monomers are mostly based on a single action mode (such as covalent or non-covalent action), which makes it difficult to achieve long-range and short-range interactions at the same time. This results in low recognition specificity of imprinted polymers for macromolecular templates (such as glycoproteins), and they are easily interfered by other molecules, especially in complex biological samples. (11) Existing functional monomer designs also lack synergy and can only provide a single mode of action, further reducing the imprinting efficiency and template recognition ability; (3) The adsorption capacity of traditional MIPs is limited because the distribution of template molecules in the polymer is restricted and the utilization rate of imprinting sites is low, which makes it difficult to meet the requirements of efficient separation and enrichment of glycoproteins; (4) MOFs materials are prone to particle aggregation and poor dispersion during preparation, and require additional separation steps, which increases the complexity of the operation; (5) The preparation and separation process of traditional MIPs is usually complex and energy-consuming, involving multiple steps such as template recovery and carrier separation, which limits the practical production applicability and economy of the technology.
[0006] The above problems urgently need to be solved through innovative design and optimization technology.
[0007] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0008] The purpose of the present invention is to provide a glycoprotein imprinted polymer based on an imidazolium ionic liquid monomer containing a boronic acid functional group, and a preparation method and application thereof, which solves the problems of insufficient recognition specificity, limited adsorption capacity, poor carrier performance and complex preparation process existing in existing glycoprotein molecular imprinted polymers, and can efficiently identify and separate glycoproteins.
[0009] In order to achieve the above object, the present invention provides a method for preparing a glycoprotein imprinted polymer based on an imidazolium ionic liquid monomer containing a boronic acid functional group, the method comprising the following steps: (1) placing lignocellulose sponge (WCS) in a reaction system of UiO-66, wherein zirconium tetrachloride (ZrCl4) and 2-aminoterephthalic acid are reacted in the reaction system to in-situ grow UiO-66 crystals on the lignocellulose sponge to prepare WCS@UiO-66; the loading amount of UiO-66 in the WCS@UiO-66 is 20 to 125%; (2) modifying the WCS@UiO-66 with methacrylic anhydride, wherein the methacrylic anhydride reacts with the amino group in the WCS@UiO-66 to introduce the carbon-carbon double bond on the methacrylic anhydride into the WCS@UiO-66 to obtain modified WCS@UiO-66; (3) The glycoprotein template is fixed on the modified WCS@UiO-66, and then the WCS@UiO-66 with the fixed glycoprotein template is polymerized with the imidazolium ionic liquid monomer PBA-IL containing a boronic acid functional group and the cross-linking agent N, N'-methylenebisacryloyl (MBA). After the reaction results, the glycoprotein template is removed and freeze-dried to obtain the glycoprotein imprinted polymer WCS@UiO-66@MIPs based on the imidazolium ionic liquid monomer containing a boronic acid functional group.
[0010] Wherein, the PBA-IL is an imidazole ionic liquid monomer containing a boronic acid functional group, and its structural formula is as follows: .
[0011] Preferably, in step (1), the lignocellulose sponge is obtained by the following method: treating the wood block at 80°C in a NaClO2 solution with a pH of 4.6 to remove lignin; treating the wood block with an aqueous solution of NaOH and Na2SO3 at 100°C to remove hemicellulose; and washing the sample and freeze-drying it to prepare the lignocellulose sponge.
[0012] Preferably, the concentration of the NaClO2 solution is 12.5 wt%; in the NaOH and Na2SO3 aqueous solutions, the concentration of NaOH is 2.5 mol·L⁻ 1 , the concentration of Na2SO3 is 0.4 mol·L⁻ 1 .
[0013] Preferably, in step (1), the WCS@UiO-66 is obtained by the following method: immersing the wood cellulose sponge in a DMF solution containing zirconium tetrachloride (ZrCl4) for coordination at room temperature; subsequently adding 2-aminoterephthalic acid (NH2-BDC) and glacial acetic acid, reacting at 120°C, washing the product and freeze-drying it to obtain WCS@UiO-66; or / and, in step (2), the modified WCS@UiO-66 is obtained by the following method: refluxing the WCS@UiO-66 with methacrylic anhydride and triethylamine in dichloromethane at 55°C, washing and vacuum drying to obtain the modified WCS@UiO-66.
[0014] Preferably, in step (3), the PBA-IL is obtained by the following method: under the protection of an inert gas atmosphere, 4-(bromomethyl)phenylboronic acid (PBA) and 1-vinyl imidazole (VIM) are refluxed in ethyl acetate at 70° C., washed and vacuum dried to obtain a PBA-IL monomer.
[0015] Preferably, in step (3), the modified WCS@UiO-66 is immersed in a phosphate buffer containing a glycoprotein template and incubated at room temperature. After the incubation is completed, the modified WCS@UiO-66 is washed to retain the WCS@UiO-66 with the fixed glycoprotein template. The WCS@UiO-66 with the fixed glycoprotein template is immersed in a phosphate buffer containing PBA-IL and N, N'-methylenebisacryl at pH 8.1, and tetramethylethylenediamine (TEMED) and ammonium persulfate (APS) are added (the redox initiation system of ammonium persulfate and tetramethylethylenediamine is used to achieve free radical initiation and polymerization), and the polymerization is stirred at room temperature. After the reaction results, the glycoprotein template is removed and freeze-dried to obtain a glycoprotein imprinted polymer WCS@UiO-66@MIPs based on an imidazolium ionic liquid monomer containing a boric acid functional group.
[0016] Preferably, in step (3), the pH of the phosphate buffer containing the glycoprotein template is 8.1; or / and, the glycoprotein template is removed by alternately washing with 0.5 M NaCl and 6.0 wt% acetic acid solution to remove the glycoprotein template; or / and, the glycoprotein template is ovalbumin (OVA).
[0017] The second object of the present invention is to provide a glycoprotein imprinted polymer based on an imidazolium ionic liquid monomer containing a boronic acid functional group. The glycoprotein imprinted polymer uses a lignocellulose sponge as a base material, and UiO-66 crystals are in situ grown on the lignocellulose sponge by reacting zirconium tetrachloride and 2-aminoterephthalic acid. The amino groups on the WCS@UiO-66 are modified by methacrylic anhydride to carry out an acylation reaction to introduce the carbon-carbon double bonds on the methacrylic anhydride to obtain modified WCS@UiO-66. The modified WCS@UiO-66 is used as a carrier to fix a glycoprotein template on the WCS@UiO-66, and a polymerization reaction is carried out with an imidazolium ionic liquid monomer PBA-IL containing a boronic acid functional group and a cross-linking agent N, N'-methylenebisacryloyl to remove the glycoprotein template, thereby distributing the glycoprotein imprinted sites on the polymer surface.
[0018] Preferably, it is obtained by the preparation method.
[0019] The third object of the present invention is to provide the use of the glycoprotein imprinted polymer based on imidazolium ionic liquid monomer containing boronic acid functional group in glycoprotein recognition and separation.
[0020] The glycoprotein imprinted polymer based on imidazolium ionic liquid monomer containing boric acid functional group of the present invention and its preparation method and application solve the problems existing in the preparation of existing glycoprotein molecular imprinted polymers, such as insufficient recognition specificity, limited adsorption capacity, poor carrier performance and complex preparation process, and has the following advantages: (1) The present invention solves the problems of insufficient recognition specificity, limited adsorption capacity, poor carrier performance and complex preparation process of existing glycoprotein molecular imprinted polymers by designing and synthesizing a functional monomer PBA-IL that has both long-range non-covalent and short-range covalent interactions, and synergistically utilizing the surface imprinting technology based on modified WCS@UiO-66 combined with the template immobilization strategy, and can efficiently identify and separate glycoproteins. (2) The present invention designs PBA-IL functional monomers so that they have both reversible covalent interactions (boronate bonds) and multiple non-covalent interactions (such as electrostatic interactions, hydrogen bonds, and π-π stacking), which significantly improves the recognition specificity and imprinting efficiency of the imprinted polymer. (3) The present invention uses lignocellulose sponge as the base material, prepares a composite carrier with high specific surface area and multiple active sites by in situ growth of UiO-66 crystals, and distributes the imprinted sites on the polymer surface in combination with surface molecular imprinting technology, effectively reducing mass transfer resistance and increasing adsorption capacity. At the same time, the lignocellulose substrate prevents MOFs particle aggregation, enhances material dispersibility and recyclability, simplifies the operation process and reduces energy consumption. By combining the template fixation method with the surface imprinting technology, the present invention further optimizes the preparation process of MIPs, making the fixation of glycoprotein templates more efficient and improving the applicability and economy in actual sample processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention is a flow chart for preparing a glycoprotein imprinted polymer based on an imidazolium ionic liquid monomer containing a boronic acid functional group.
[0022] Figure 2 The ionic liquid monomer PBA-IL prepared in Example 1 of the present invention 1 H NMR spectrum.
[0023] Figure 3 This is the FTIR spectrum in Experimental Example 1 of the present invention.
[0024] Figure 4 This is the XPS spectrum in Experimental Example 1 of the present invention.
[0025] Figure 5 This is the XRD spectrum in Experimental Example 1 of the present invention.
[0026] Figure 6 This is the TGA curve in Experimental Example 1 of the present invention.
[0027] Figure 7 This is the comparison result of the adsorption performance of WCS@UiO-66@MIPs with different MOF loading amounts in Experimental Example 2 of the present invention.
[0028] Figure 8Adsorption isotherms of WCS@UiO-66@MIPs, WCS@UiO-66@NIPs, WCS@UiO-66@MIPs-0 and WCS@UiO-66@NIPs-0 in Experimental Example 3 of the present invention; (a) Langmuir isotherm; (b) Freundlich isotherm.
[0029] Fig. 9 The figure shows the SDS-PAGE analysis result of the protein of the present invention adsorbing to MIPs.
[0030] Note: The WCS@UiO-66 in the figure is WCS@UiO-66 modified by methacrylic anhydride. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.
[0033] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0034] The features mentioned in the present invention can be combined arbitrarily, as long as there is no contradiction in the combination of these features, all possible combinations should be considered as the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.
[0035] The present invention provides a glycoprotein imprinted polymer based on imidazolium ionic liquid monomer containing boronic acid functional group and its preparation method and application. Aiming at the problems of insufficient recognition specificity, limited adsorption capacity, poor carrier performance and complicated preparation process of existing glycoprotein molecular imprinted polymers MIPs, an innovative technical solution based on imidazolium ionic liquid functional monomer containing boronic acid functional group (PBA-IL) and wood cellulose sponge loaded UiO-66 composite carrier (WCS@UiO-66) is proposed (see Figure 1), to achieve highly selective recognition and efficient separation of glycoprotein molecules, aiming to address the shortcomings of existing glycoprotein molecular imprinting polymers in recognition specificity, adsorption capacity and practical application performance.
[0036] The glycoprotein imprinted polymer WCS@UiO-66@MIPs based on the imidazolium ionic liquid monomer containing boronic acid functional group of the present invention is designed and synthesized with the functional monomer PBA-IL having both long-range non-covalent and short-range covalent interactions, so that it has both reversible covalent action (boronate bond) and multiple non-covalent actions (such as electrostatic action, hydrogen bond, π-π stacking), which significantly improves the recognition specificity and imprinting efficiency of the imprinted polymer. The lignocellulose sponge is used as the base material. The lignocellulose sponge has rich pore structure and excellent mechanical properties. Its derivatives can be directly applied to the permeation and filtration process, thereby realizing the efficient separation and purification of the target substance, which not only significantly improves the separation efficiency and selectivity, but also simplifies the separation process and reduces energy consumption. The present invention prepares a composite carrier with high specific surface area and multiple active sites by in-situ growth of UiO-66 crystals on the lignocellulose sponge, and combines the surface molecular imprinting technology to distribute the imprinting sites on the polymer surface, effectively reducing the mass transfer resistance and improving the adsorption capacity. At the same time, the lignocellulose substrate prevents MOFs particle aggregation, enhances material dispersibility and recyclability, simplifies the operation process and reduces energy consumption.
[0037] By combining the template fixation method with the surface imprinting technology, the present invention further optimizes the preparation process of MIPs, makes the fixation of the glycoprotein template more efficient, and improves the applicability and economy in actual sample processing.
[0038] The WCS@UiO-66@MIPs of the present invention adsorbed proteins and then desorbed as follows: the template protein was removed by washing with 0.5 M NaCl solution and 6.0 wt% acetic acid solution alternately at 25°C for several times. Finally, the WCS@UiO-66@MIPs were washed with deionized water and freeze-dried to obtain the WCS@UiO-66@MIPs that can be recovered and reused. The eluate was combined with dialysis desalination to obtain the recovery of the adsorbed protein.
[0039] The glycoprotein imprinted polymer based on imidazolium ionic liquid monomer containing boronic acid functional group provided by the present invention and its preparation method and application are described in detail below through examples, comparative examples and experimental examples.
[0040] Example 1 A glycoprotein imprinted polymer based on an imidazolium ionic liquid monomer containing a boronic acid functional group, wherein the preparation method comprises: 1) Preparation of lignocellulose sponge The wood blocks were ultrasonically cleaned with ethanol and dried at 80 °C for 6 h, and then lignin and hemicellulose were removed by NaClO2 and NaOH solutions, respectively. The specific steps were as follows: About 4 g of wood blocks were immersed in 1000 mL of 12.5 wt% NaClO2 aqueous solution with a pH of 4.6 (the pH was adjusted with acetic acid) and treated at 80°C for 8 hours to remove lignin. The obtained samples were collected and washed with deionized water; they were treated with NaOH (2.5 mol·L⁻¹) and Na2SO3 (0.4 mol·L⁻¹) solutions at 100°C for 8 hours to remove hemicellulose; the samples were washed with ethanol-water solution and freeze-dried to prepare high-porosity wood cellulose sponge. The prepared WCS had a specific surface area of 16.1 m² / g, a pore volume of 0.023 cm³ / g, and an average pore size of 4.8 nm.
[0041] 2) Preparation of WCS@UiO-66 composites The in situ growth method of UiO-66 crystals was used to prepare the composites. In order to optimize the performance of the composites, DMF solutions containing different amounts of ZrCl4 (0.1004, 0.1506, 0.2008, 0.2510 and 0.3012 g) were used to prepare composites with different MOF loadings, as follows: (a) The WCS prepared above was immersed in 15 mL of DMF solution containing ZrCl4, and the zirconium ions coordinated with the cellulose hydroxyl groups at room temperature for 1 hour; then 0.2510 g of NH2-BDC organic ligand and 4 mL of glacial acetic acid were added in sequence, and the reaction was carried out at 120°C for 24 hours. The product was separated from the solution, washed several times (using methanol, DMF and deionized water to remove residual reagents and unbound UiO-66) and freeze-dried to obtain the WCS@UiO-66 composite material;
[0042] (b) 400 mg of WCS@UiO-66 composite material was reacted with 2.46 g of methylacrylic anhydride and 0.20 g of triethylamine in 50 mL of dichloromethane at reflux at 55 °C for 24 h. After washing with chloroform, the composite materials were dried in a vacuum oven at 60 °C to obtain composite materials with different MOF (i.e., UiO-66) loadings, which were named WCS@UiO-66-I, WCS@UiO-66-II, WCS@UiO-66-III, WCS@UiO-66-IV and WCS@UiO-66-V, with MOF loadings of 20%, 45%, 82%, 101% and 125%, respectively.
[0043] 3) Preparation of Boric Acid-containing Imidazolium Ionic Liquid Monomer (PBA-IL) Under nitrogen protection, PBA and 1-vinyl imidazole were refluxed in ethyl acetate at 70 ° C for 24 hours, washed and vacuum dried to obtain PBA-IL monomer, which was used 1 H NMR confirmed its chemical structure, 1 H NMR see Figure 2 The pKa value of this product was determined to be 7.9 at room temperature.
[0044] 4) Preparation of glycoprotein imprinted polymer (WCS@UiO-66@MIPs) The preparation method of the glycoprotein imprinted polymer is as follows: (A) Template fixation: The WCS@UiO-66 prepared above was immersed in a phosphate buffer containing OVA (2 mg·mL⁻¹, pH 8.1) and incubated at room temperature for 3 hours. After washing, the WCS@UiO-66 with the fixed OVA template was retained; (B) Surface imprinting polymerization: OVA-immobilized WCS@UiO-66 was immersed in a phosphate buffer (pH 8.1) containing PBA-IL and MBA (N, N'-methylenebisacryloyl), TEMED and APS were added, and polymerization was stirred at 25°C for 24 h. (C) Template removal: The template protein was removed by alternating washing with 0.5 M NaCl and 6.0 wt% acetic acid solution, and finally freeze-dried to obtain WCS@UiO-66@MIPs.
[0045] Comparative Example 1 The preparation of non-imprinted material (WCS@UiO-66@NIPs) is basically the same as Example 1, except that: No OVA template was added during the preparation of the imprinted polymer.
[0046] Comparative Example 2 The method is basically the same as that of Example 1, except that: PBA-IL was replaced with the traditional monomer VBA (4-vinylbenzeneboronic acid) to prepare the imprinted material WCS@UiO-66@MIPs-0 and the non-imprinted material WCS@UiO-66@NIPs-0.
[0047] Experimental Example 1 Material structure characterization experiment 1. FTIR analysis WCS@UiO-66@MIPs were characterized by FTIR. Figure 3The results showed that WCS had characteristic peaks of cellulose (895 cm⁻¹, 1056 cm⁻¹, 2912 cm⁻¹, 3423 cm⁻¹), and WCS@UiO-66 had characteristic peaks at 669 cm⁻¹ (Zr–O) and 1577 cm⁻¹, 1434 cm⁻¹ and 1380 cm⁻¹ (UiO-66 benzene ring), proving that the composite material was successfully synthesized. The new peaks of WCS@UiO-66@MIPs at 1548 cm⁻¹ (C–N), 1421 cm⁻¹ (B–O) and 1371 cm⁻¹ (C–B) confirmed that PBA-IL was successfully introduced into the imprinting layer.
[0048] 2. XPS analysis XPS results are shown in Figure 4 The results show that WCS only contains characteristic peaks of C and O elements, while WCS@UiO-66 adds N 1s (399.11 eV) and Zr 3d, 3p, 3s (182.12, 346.17, 333.17, 431.17 eV) characteristic peaks, proving that UiO-66 was successfully introduced. WCS@UiO-66@MIPs further showed B 1s (197.97 eV) characteristic peaks, corresponding to the OBO functional group in PBA-IL, confirming that the imprinted material was successfully synthesized.
[0049] 3. XRD analysis XRD results are shown in Figure 5 The results show that WCS exhibits characteristic diffraction peaks of cellulose I structure at 2θ=14.8°~16.8° and 22.5°. WCS@UiO-66 adds new characteristic peaks of UiO-66 crystal (7.34° and 8.45°), indicating that UiO-66 is successfully grown in situ in the WCS matrix. There is no significant change in the XRD spectra of WCS@UiO-66 and WCS@UiO-66@MIPs, indicating that the crystal structure of UiO-66 is not damaged during the construction of the imprinting layer.
[0050] 4. TGA analysis TGA results are shown in Figure 6 , TGA showed that WCS lost 76.3% due to thermal decomposition of cellulose at 240~380℃. The thermal weight loss of UiO-66 was divided into 30~250℃ (solvent evaporation), 250~560℃ (organic ligand decomposition) and >560℃ (metal ion oxidation). WCS@UiO-66 showed composite characteristics, and the 45.9% weight loss at 250~540℃ was attributed to the decomposition of cellulose and ligands and Zr-O dehydroxylation. The mass loss of WCS@UiO-66@MIPs reached 72.4%, which was higher than 61.2% of WCS@UiO-66, further proving the successful construction of the imprinted layer.
[0051] 5. BET Analysis BET results show that the specific surface area of WCS is 16.1 m² / g, which significantly increases to 62.4 m² / g for WCS@UiO-66, and even though it decreases slightly, it still reaches 50.3 m² / g for WCS@UiO-66@MIPs. The excellent pore structure supports the efficient recognition and adsorption of proteins.
[0052] Experimental Example 2 Comparison of adsorption performance of WCS@UiO-66@MIPs with different MOF loadings At 25 °C, 10 mg of WCS@UiO-66@MIPs with different MOF loadings were incubated in 10 mL of 10 mM phosphate buffer solution (pH 8.1) (containing 1.0 mg mL -1 After 40 minutes of incubation, the remaining concentration of OVA in the solution was measured using a 280 nm UV-visible spectrophotometer.
[0053] The adsorption amount of template protein by WCS@UiO-66@MIPs was calculated according to formula (1): Q : (1) In formula (1), they represent the initial concentration of protein in the solution ( C 0 ) and residual concentration ( C e ) (mg mL⁻¹), V represents the volume of the protein solution (mL), m It represents the mass of adsorbent (mg).
[0054] like Figure 7 The figure shows the adsorption performance comparison results of WCS@UiO-66@MIPs with different MOF loadings. It can be seen that the adsorption capacity of MIPs increases first and then decreases with the UiO-66 loading. At high concentrations, the accumulation of excessive UiO-66 crystals hinders the elution and rebinding of proteins, resulting in performance degradation. The adsorption performance of WCS@UiO-66@MIPs prepared by WCS@UiO-66-IV is the best, so subsequent experiments will further study the performance of WCS@UiO-66@MIPs prepared by WCS@UiO-66-IV as a carrier.
[0055] Experimental Example 3 Comparison of specificity and adsorption performance of molecularly imprinted and non-molecularly imprinted materials prepared from different monomers At 25 °C, 10 mg of WCS@UiO-66@MIPs (or WCS@UiO-66@NIPs) was incubated in 10 mL of 10 mM phosphate buffer solution (pH 8.1) containing 1.0 mg mL -1After 40 minutes of incubation, the remaining concentration of OVA in the solution was measured using a UV-visible spectrophotometer at 280 nm.
[0056] According to the above formula (1), the adsorption amount of template protein by WCS@UiO-66@MIPs (or WCS@UiO-66@NIPs) was calculated: Q .
[0057] imprinting factor IF ) is used to evaluate the recognition ability of MIPs, and its calculation is shown in formula (2): (2) In formula (2), MIPs and NIPs Represent the adsorption amount of template protein by WCS@UiO-66@MIPs and WCS@UiO-66@NIPs, respectively.
[0058] like Figure 8 As shown in the figure, the effect of different initial OVA concentrations on the adsorption capacity of MIPs and NIPs based on different functional monomers is demonstrated. The results show that the adsorption capacity of both MIPs is higher than that of the corresponding NIPs in all concentration ranges, confirming the successful formation of the imprinted cavity. In addition, the equilibrium adsorption capacity of all adsorbents increases with the increase of initial OVA concentration. Specifically, WCS@UiO-66@MIPs and WCS@UiO-66@MIPs-0 have a higher adsorption capacity than the corresponding NIPs at a protein concentration of 1.3 mg·mL -1 and 1.2 mg mL -1 The saturated adsorption was reached at 571 mg·g -1 and 232 mg·g -1 , the corresponding imprinting factor ( IF ) are 5.09 and 3.03. The superior recognition and maximum adsorption capacity of WCS@UiO-66@MIPs may be due to the formation of more prepolymer complexes between PBA-IL and OVA during the preparation of MIPs, resulting in a greater abundance of imprinted cavities.
[0059] Moreover, the adsorption rate of WCS@UiO-66@MIPs prepared in the present invention was significantly better than that of WCS@UiO-66@MIPs-0 within 20 min, and equilibrium was reached within 40 min, which was attributed to the stronger non-covalent interaction between PBA-IL and OVA, while the other materials required 60 min.
[0060] Comprehensively comparing the adsorption rate, capacity and recognition, WCS@UiO-66@MIPs showed significant advantages, verifying the synergistic effect of PBA-IL and TIS-PN-co-SIT strategy in protein imprinting.
[0061] Experimental Example 4 Competitive adsorption experiment In the actual sample competition adsorption experiment using egg white as the protein source, the specific process is as follows: First, the egg white was diluted 3 times with phosphate buffer (pH 8.1, concentration 10 mM). Subsequently, about 10 mg of WCS@UiO-66@MIPs or WCS@UiO-66@MIPs-0 was added to 10 mL of the diluted egg white solution at 25°C and the reaction was continued for 50 minutes. Next, the reaction product was placed in an environment of 25°C and treated with 0.5 M sodium chloride and 6.0 wt% acetic acid solution to remove the adsorbed protein. The elution process continued until the characteristic peak of the protein was no longer observed in the UV spectrum. After that, the components of the adsorbed protein were combined and desalted using a dialysis bag with a molecular weight cutoff of 500 Da, and then freeze-dried by freeze-drying. Finally, 0.5 mL of phosphate buffer (0.01 M, pH 7.0) was used to dissolve the obtained product. The samples were analyzed by SDS-PAGE technique (SDS polyacrylamide gel electrophoresis) containing 12.5% polyacrylamide separating gel and 5% polyacrylamide stacking gel.
[0062] like Fig. 9 The following is the SDS-PAGE analysis result of protein adsorption to MIPs. In the figure, OVT is ovotransferrin, Lane 1 is a protein molecule marker (10-150 kDa), Lane 2 is a 30-fold dilution of egg white, Lanes 3 and 4 are proteins eluted from WCS@UiO-66@MIPs and WCS@UiO-66@MIPs-0, Lanes 5 and 6 are proteins eluted from WCS@UiO-66@MIPs-1 and WCS@UiO-66@MIPs-2, respectively. 6 are the supernatants after adsorption of WCS@UiO-66@MIPs and WCS@UiO-66@MIPs-0, respectively. It can be seen that both WCS@UiO-66@MIPs and WCS@UiO-66@MIPs-0 of the present invention can achieve the adsorption of OVA. The WCS@UiO-66@MIPs of the present invention is not interfered by other proteins such as OVT, and has good recognition specificity. Moreover, the adsorption amount of OVA by WCS@UiO-66@MIPs is obviously greater than that of WCS@UiO-66@MIPs-0.
[0063] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing a glycoprotein imprinted polymer based on an imidazolium ionic liquid monomer containing a boronic acid functional group, characterized in that: The method comprises the following steps: (1) placing a cellulose sponge in a UiO-66 reaction system, wherein zirconium tetrachloride and 2-aminoterephthalic acid are reacted in the reaction system, and UiO-66 crystals are in situ grown on the cellulose sponge to prepare WCS@UiO-66; wherein the loading amount of UiO-66 in the WCS@UiO-66 is 20 to 125%; (2) modifying the WCS@UiO-66 with methacrylic anhydride, wherein the methacrylic anhydride reacts with the amino group in the WCS@UiO-66 to introduce the carbon-carbon double bond on the methacrylic anhydride into the WCS@UiO-66 to obtain modified WCS@UiO-66; (3) Fixing a glycoprotein template on the modified WCS@UiO-66, and then polymerizing the WCS@UiO-66 with the fixed glycoprotein template with a boronic acid functional group-containing imidazolium ionic liquid monomer PBA-IL and a cross-linking agent N, N'-methylenebisacrylamide, removing the glycoprotein template after the reaction is completed, and freeze-drying to obtain a glycoprotein imprinted polymer WCS@UiO-66@MIPs based on a boronic acid functional group-containing imidazolium ionic liquid monomer; Wherein, the PBA-IL is an imidazole ionic liquid monomer containing a boronic acid functional group, and its structural formula is as follows: 。 2. The preparation method according to claim 1, characterized in that: In step (1), the lignocellulose sponge is obtained by the following method: The wood blocks were treated at 80°C in a NaClO2 solution with a pH of 4.6 to remove lignin. They were then treated with NaOH and Na2SO3 aqueous solutions at 100°C to remove hemicellulose. The samples were washed and freeze-dried to prepare lignocellulose sponges.
3. The preparation method according to claim 2, characterized in that: The concentration of the NaClO2 solution is 12.5 wt%; in the NaOH and Na2SO3 aqueous solutions, the concentration of NaOH is 2.5 mol·L⁻ 1 , the concentration of Na2SO3 is 0.4 mol·L⁻ 1 .
4. The preparation method according to claim 1, characterized in that: In step (1), the WCS@UiO-66 is obtained by the following method: The lignocellulose sponge was immersed in a DMF solution containing zirconium tetrachloride and coordinated at room temperature; then 2-aminoterephthalic acid and glacial acetic acid were added and reacted at 120°C. The product was washed and freeze-dried to obtain WCS@UiO-66; Or / and, in step (2), the modified WCS@UiO-66 is obtained by the following method: The WCS@UiO-66 was reacted with methacrylic anhydride and triethylamine in dichloromethane at 55° C. under reflux, and then washed and vacuum dried to obtain modified WCS@UiO-66.
5. The preparation method according to claim 1, characterized in that: In step (3), the PBA-IL is obtained by the following method: Under the protection of an inert gas atmosphere, 4-(bromomethyl)phenylboronic acid and 1-vinylimidazole were refluxed in ethyl acetate at 70° C., washed and dried in vacuo to obtain a PBA-IL monomer.
6. The preparation method according to claim 1, characterized in that: In step (3), the modified WCS@UiO-66 is immersed in a phosphate buffer containing a glycoprotein template and incubated at room temperature. After the incubation is completed, the modified WCS@UiO-66 is washed to retain the WCS@UiO-66 with the fixed glycoprotein template. The WCS@UiO-66 with the fixed glycoprotein template is immersed in a phosphate buffer containing PBA-IL and N, N'-methylenebisacryl at pH 8.1, tetramethylethylenediamine and ammonium persulfate are added, and the polymerization is stirred at room temperature. After the reaction is completed, the glycoprotein template is removed and freeze-dried to obtain a glycoprotein imprinted polymer WCS@UiO-66@MIPs based on an imidazolium ionic liquid monomer containing a boric acid functional group.
7. The preparation method according to claim 6, characterized in that: In step (3), the pH of the phosphate buffer containing the glycoprotein template is 8.1; or / and, the removing of the glycoprotein template comprises washing with 0.5 M NaCl and 6.0 wt % acetic acid solution alternately to remove the glycoprotein template; Or / and, the glycoprotein template is ovalbumin OVA.
8. A glycoprotein imprinted polymer based on imidazolium ionic liquid monomers containing boronic acid functional groups, characterized in that: The glycoprotein imprinted polymer uses cellulose sponge as a substrate material, and UiO-66 crystals are in situ grown on the cellulose sponge by reacting zirconium tetrachloride and 2-aminoterephthalic acid. The amino groups on the WCS@UiO-66 are modified by methacrylic anhydride and an acylation reaction is performed to introduce the carbon-carbon double bonds on the methacrylic anhydride to obtain modified WCS@UiO-66. The modified WCS@UiO-66 is used as a carrier to fix a glycoprotein template on the WCS@UiO-66, and a polymerization reaction is carried out with a boric acid functional group-containing imidazole ionic liquid monomer PBA-IL and a cross-linking agent N, N'-methylenebisacryl to remove the glycoprotein template, thereby distributing the glycoprotein imprinting sites on the polymer surface.
9. The glycoprotein imprinted polymer based on imidazolium ionic liquid monomer containing boronic acid functional group according to claim 8, characterized in that: The method is obtained by the preparation method as described in any one of claims 1 to 6.
10. Use of the glycoprotein imprinted polymer based on imidazolium ionic liquid monomer containing boronic acid functional group as claimed in claim 8 or 9 in glycoprotein recognition and separation.